Effects of Implementation and Enforcement Differences in Prescription Drug Monitoring Programs in 3 States: Connecticut, Kentucky, and Wisconsin. (March 2021) - Dickson-Gomez, Julia; Christenson, Erika; Weeks, Margaret; Galletly, Carol; Wogen, Jennifer; Spector, Antoinette; McDonald, Madelyn; Ohlrich, Jessica
Background and aims: Prescription Drug Monitoring Programs (PDMPs) were designed to curb opioid misuse and diversion by tracking scheduled medications prescribed by medical providers and dispensed by pharmacies. The effects of PDMPs on opioid prescription, misuse and overdose rates have been mixed due in part to variability in states' PDMPs and difficulties measuring this complexity, and a lack of attention to implementation and enforcement of PDMP components. The current study uses qualitative interviews with key informants from 3 states with different PDMPs, Connecticut, Kentucky and Wisconsin to explore differences in the characteristics of the PDMPs in each state; how they are implemented, monitored and enforced; and unintended negative consequences of these programs. Methods: We conducted in-depth interviews with key informants from each state representing the following sectors: PDMP and pain clinic regulation agencies, Medicaid programs, state licensing boards, pharmacies, emergency medicine departments, pain management clinics, first responders, drug courts, drug treatment programs, medication assisted treatment (MAT) providers, and harm reduction organizations. Interview guides explored participants' experiences with and opinions of PDMPs according to their roles. Data analysis was conducted using a collaborative, constant comparison method. Results: While all 3 states had mandated registration and reporting requirements, the states differed in the implementation and enforcement of these and the extent to which provider prescribing was monitored. These, in turn, influenced how medical providers perceived the PDMP and changed how providers prescribed opioids. Unintended consequences of state PDMPs included under-prescribing for pain and "dumping" patients who were long term users of opioids or who had developed opioid use disorders and may explain the increase in illicit heroin or opioid use. Conclusion: State PDMPs with similar mandates may differ greatly in implementation and enforcement. These differences are important to consider when determining the effects of PDMPs on opioid misuse and overdose.